2022
DOI: 10.7819/rbgn.v24i2.4170
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Brand Understanding Through Brand Training: a Conditional Process Analysis of Recent Hires at an Airline

Abstract: Purpose -Within internal branding research, the positive association between employee brand training and brand understanding is well established. However, the boundary conditions of this focal relationship have not been researched to date, and insights about the effect of individual differences would be of significant practical value to service organizations. Accordingly, the purpose of this study is to test the moderating effect on the focal relationship of three key individual differences: age, gender, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…These studies confirm that brand training is the proximal driver of brand understanding (King & So, 2015;Murillo & King, 2019;Murillo, 2022). Furthermore, recent studies taking a more fine-grained longitudinal view have shown that even for simple jobs, such as restaurant servers, a thorough grasp of the desired customer experience (i.e., the brand promise) and their role in delivering it can take months to be fully internalized, thus emphasizing the importance of a sustained training effort (Murillo & King, 2019).…”
Section: Internal Branding Processes In a Fashion Organization: Turni...supporting
confidence: 60%
See 2 more Smart Citations
“…These studies confirm that brand training is the proximal driver of brand understanding (King & So, 2015;Murillo & King, 2019;Murillo, 2022). Furthermore, recent studies taking a more fine-grained longitudinal view have shown that even for simple jobs, such as restaurant servers, a thorough grasp of the desired customer experience (i.e., the brand promise) and their role in delivering it can take months to be fully internalized, thus emphasizing the importance of a sustained training effort (Murillo & King, 2019).…”
Section: Internal Branding Processes In a Fashion Organization: Turni...supporting
confidence: 60%
“…This empirical study of employees at a sportswear fashion firm tested internal branding relationships that have been previously validated in studies from various service industries (Buil et al, 2016;Du Preez et al, 2017;Huang & Lai, 2018;Murillo, 2022;Taku et al, 2022;Terglav et al, 2016). Survey results show strong support for nearly all of the hypothesized relationships (even with brand identification mediated by brand commitment), suggesting that internal branding practices, as implemented in fashion organizations, deserve greater research attention to build a holistic understanding of the profile and role of employee brand ambassadors in the fashion industry, and the best ways of recruiting, training and leading them, a topic which the fashion literature has yet to examine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation